Knowledge And Practice on Prevention and Control of Dengue Among Homemaker in Bharatpur Metropolitan, Chitwan (International Journal of Silkroad Institute of Research and Training, 2023)
Background: Dengue is a viral infection transmitted to humans through the bite of infected mosquitoes. The dengue virus (DENV) is one of the mosquito-borne viral diseases in the world today. Two main arthropod vectors are responsi-ble for transmission of dengue viruses: Aedes aegypti and Aedes albopictus. The Aedes aegypti mosquito is the main vector for the spread of dengue fever.Methods: An analytical cross-sectional study was conducted among home makers of Bharatpur. Data was analyzed using descriptive and inferential statistical tools in SPSS-20. p-value